Characterization of a novel PERK kinase inhibitor with antitumor and antiangiogenic activity - Atkins, Charity; Liu, Qi; Minthorn, Elisabeth; Zhang, Shu-Yun; Figueroa, David J; Moss, Katherine; Stanley, Thomas B; Sanders, Brent; Goetz, Aaron; Gaul, Nathan; Choudhry, Anthony E; Alsaid, Hasan; et al. (Cancer research (Chicago, Ill.), 2013)
The unfolded protein response (UPR) is a signal transduction pathway that coordinates cellular adaptation to microenvironmental stresses that include hypoxia, nutrient deprivation, and change in redox status. These stress stimuli are common in many tumors and thus targeting components of the UPR signaling is an attractive therapeutic approach. We have identified a first-in-class, small molecule inhibitor of the eukaryotic initiation factor 2-alpha kinase 3 (EIF2AK3) or PERK, one of the three mediators of UPR signaling. GSK2656157 is an ATP-competitive inhibitor of PERK enzyme activity with an IC(50) of 0.9 nmol/L. It is highly selective for PERK with IC(50) values >100 nmol/L against a panel of 300 kinases. GSK2656157 inhibits PERK activity in cells with an IC(50) in the range of 10-30 nmol/L as shown by inhibition of stress-induced PERK autophosphorylation, eIF2α substrate phosphorylation, together with corresponding decreases in ATF4 and CAAT/enhancer binding protein homologous protein (CHOP) in multiple cell lines. Oral administration of GSK2656157 to mice shows a dose- and time-dependent pharmacodynamic response in pancreas as measured by PERK autophosphorylation. Twice daily dosing of GSK2656157 results in dose-dependent inhibition of multiple human tumor xenografts growth in mice. Altered amino acid metabolism, decreased blood vessel density, and vascular perfusion are potential mechanisms for the observed antitumor effect. However, despite its antitumor activity, given the on-target pharmacologic effects of PERK inhibition on pancreatic function, development of any PERK inhibitor in human subjects would need to be cautiously pursued in cancer patients.